Test-Retest Reliability of a Serious Game for Delirium Screening in the Emergency Department - Tong, Tiffany; Chignell, Mark; Tierney, Mary C.; Lee, Jacques S. (Frontiers in Aging Neuroscience, 2016)
Introduction: Cognitive screening in settings such as emergency departments (ED) is frequently carried out using paper-and-pencil tests that require administration by trained staff. These assessments often compete with other clinical duties and thus may not be routinely administered in these busy settings. Literature has shown that the presence of cognitive impairments such as dementia and delirium are often missed in older ED patients. Failure to recognize delirium can have devastating consequences including increased mortality (Kakuma et al., 2003). Given the demands on emergency staff, an automated cognitive test to screen for delirium onset could be a valuable tool to support delirium prevention and management. In earlier research we examined the concurrent validity of a serious game, and carried out an initial assessment of its potential as a delirium screening tool (Tong et al., 2016). In this paper, we examine the test-retest reliability of the game, as it is an important criterion in a cognitive test for detecting risk of delirium onset. Objective: To demonstrate the test-retest reliability of the screening tool over time in a clinical sample of older emergency patients. A secondary objective is to assess whether there are practice effects that might make game performance unstable over repeated presentations. Materials and Methods: Adults over the age of 70 were recruited from a hospital ED. Each patient played our serious game in an initial session soon after they arrived in the ED, and in follow up sessions conducted at 8-h intervals (for each participant there were up to five follow up sessions, depending on how long the person stayed in the ED). Results: A total of 114 adults (61 females, 53 males) between the ages of 70 and 104 years (M = 81 years, SD = 7) participated in our study after screening out delirious patients. We observed a test-retest reliability of the serious game (as assessed by correlation r-values) between 0.5 and 0.8 across adjacent sessions. Conclusion: The game-based assessment for cognitive screening has relatively strong test-retest reliability and little evidence of practice effects among elderly emergency patients, and may be a useful supplement to existing cognitive assessment methods.